Periodontal treatment performed before, during, or after orthodontic therapy: Perawatan periodontal yang dilakukan sebelum, pada saat, atau setelah terapi ortodontik - Ummi Salmiah Sari; Mardiana Andi Adam (Makassar Dental Journal, 2024)
Periodontal tissue health is fundamental to any type of dental treatment. One of them is orthodontic treatment. Orthodontic treat-ment can usually cause periodontal problems such as gingival inflammation, gingival recession, gingival pockets and bone des-truction. This literature review discusses several types of periodontal treatments that can be performed before, during or after ortho-dontic treatment using PubMed, Wiley and Google Scholar sources. Several studies stated that periodontal treatment can be performed before, during or after orthodontic therapy. It was concluded that orthodontic treatment usually encounters problems in patients with periodontal disease and can be a predisposing factor for the onset of periodontal disease. The risk factors for this condition are influenced by oral hygiene, control time, and duration of orthodontic treatment. The periodontal-orthodontic care linkage is very important before, during or after orthodontic therapy.